Communication Strategies and Cognitive Demand in Mathematical Task Enactment: Reflections from the Classroom - Yabas, Defne; Altun, Sertel (HACETTEPE UNIV, 2020)
Learning opportunities presented to students through various mathematical tasks can differ. Cognitive demand concept defines the degree of thinking, reasoning and problem-solving opportunities offered to students through a mathematical task. Over a class period, the cognitive demand of a mathematical task can change in set-up and implementation phases. Scaffolding, encouraging students to give explanations, justification, questioning and making comments, etc. are factors associated with the change in cognitive demand. These factors are also related to in-class mathematical communication. Therefore, cognitive demand of tasks can be affected from teachers' task presentation, guidance provided, and environment created for mathematical discussions. From this point on, the study aims to explore the interactions between cognitive demand and mathematical communication during the enactment of a mathematical task. Employing a case study design, the study included two 4th grade teachers and their 37 students from a private school in Istanbul. Data from classroom observations were complemented with the researchers' field notes. Results indicated that, cognitive demand and mathematical communication had a reciprocal relationship during enactment, and to achieve positive results with students, cognitive demand level of chosen mathematical tasks, guiding behavior of teachers and mathematical communication environment should be considered.
Keywords: Mathematical communication; cognitive demand; teaching mathematics; learning tasks; CURRICULUM MATERIALS; TEACHERS KNOWLEDGE; THINKING; REFORM; CONTEXT; COMPETENCE; DISCOURSE; PATTERNS; SUPPORT; Education & Educational Research